PENGENALAN TEKNIK FOTOGRAFI UNTUK MEDIA SOSIAL WIRAUSAHA PADA SISWA SMP TARSISIUS I - Puspitowati, Ida (Jurnal Bakti Masyarakat Indonesia, 2023)
The contribution of entrepreneurship to the economy has a big role. To increase the role of entrepreneurship ineconomic growth, it is necessary to introduce entrepreneurial activities from an early age. Tarsisius 1 MiddleSchool, West Jakarta introduces entrepreneurial activities to students through extracurricular activities or throughintra-curricular activities such as arts/crafts subjects, where the results of crafts can be directed into entrepreneurialactivities. Social media currently plays a very important role in entrepreneurial activities, to introduce products toconsumers, in line with the development of digitalization in the economy. Efforts to increase the role of social medianeed to be supported by displaying product photos so that they can attract potential buyers to the goods produced.The aim of understanding in increasing the role of social media in young entrepreneurs, at junior high school level,can be done by providing an introduction to techniques for taking product photos to attract potential buyers, throughbroadcasts on students' social media. Assistance to partners through the introduction of photography techniques iscarried out by the Abdimas team by providing an understanding of the importance of promotion via social media bydisplaying product photos that are more attractive to potential consumers. The appearance of photos on socialmedia will be more attractive by using appropriate photography techniques according to product promotionalpurposes. Apart from understanding the importance of promotion on social media using photography techniques,creativity is needed to support promotion. As a result of the introduction to photography techniques provided,through short practice and encouraging students to keep trying, Tarsisius I Middle School students were able to takebetter photos for later use in product promotion via social media. By using simple tools that students have,smartphones or simple cameras that they have, photo displays can be created attractively through the use ofappropriate photography techniques. The Undergraduate Management Study Program and the Institute for Researchand Community Service at Universitas Tarumanagara are collaborating with Tarsisius 1 Middle School, WestJakarta, to carry out activities to introduce photography techniques for social media, entrepreneurial activities forTarsisius 1 Middle School students, in order to stimulate creativity in displaying products and at the same timesupport them in carrying out entrepreneurial activities. ABSTRAKKontribusi wirausaha pada perekonomian memiliki peran yang besar. Untuk meningkatkan peran wirausaha dalampertumbuhan ekonomi diperlukan pengenalan kegiatan wirausaha sejak dini. SMP Tarsisius 1 Jakarta Baratmemperkenalkan kegiatan wirausaha pada siswa melalui kegiatan ekstrakurikuler ataupun melalui kegiatan intrakurikuler seperti mata pelajaran seni/ prakarya. Media sosial saat ini sangat berperan penting dalam kegiatanwirausaha, untuk memperkenalkan produk bagi konsumen, sejalan dengan perkembangan digitalisasi dalamperekonomian. Tujuan pemahaman dalam peningkatan peran media sosial pada wirausaha muda, jenjang SMP, dapatdilakukan dengan memberikan pengenalan teknik pengambilan foto produk agar menarik calon pembeli, melaluitayangan pada media sosial yang dimiliki oleh siswa. Pendampingan kepada mitra melalui pengenalan teknikfotografi dilakukan oleh tim Abdimas dengan memberikan pemahaman pentingnya promosi melalui media sosialdengan cara menampilkan foto produk lebih menarik bagi calon konsumen. Disamping pemahaman pentingnyapromosi di media sosial dengan teknik fotografi, perlu adanya kreativitas untuk mendukung promosi. Hasil daripengenalan teknik fotografi yang diberikan, melalui praktek singkat serta dorongan siswa untuk terus mencoba,siswa SMP Tarsisius I dapat melakukan pengambilan foto lebih baik untuk selanjutnya digunakan dalam promosihasil produk melalui media sosial. Dengan menggunakan alat sederhana yang dimiliki siswa, smartphone ataupunkamera sederhana yang dimiliki, tampilan foto dapat dibuat dengan menarik. Program Studi Sarjana Manajemen danLembaga Penelitian dan Pengabdian Masyarakat Universitas Tarumanagara bekerja sama dengan Sekolah MenengahPertama Tarsisius 1 Jakarta Barat untuk melakukan kegiatan pengenalan teknik fotografi untuk media sosial kegiatanwirausaha Siswa SMP Tarsisius 1, agar dapat merangsang kreativitas dalam menampilkan produk dan sekaligusmendukung dalam melakukan kegiatan kewirausahaan.